Sun never sets : South Asian migrants in an age of U.S. power (Orient Blackswan, 2013)
The Sun Never Sets collects the work of a generation of scholars who are enacting a shift in the orientation of the field of South Asian American studies. By focusing upon the lives, work, and activism of specific, often unacknowledged, migrant populations, the contributors present a more comprehensive vision of the South Asian presence in the United States.